Analisis Kelayakan Air Berbasis Android - Alia Sutarwiah; Alfit Fajri B; Faisal Abda’oe; Fredly Deviano B; M. Ali Dermawan; Restu Mukti Utomo (PTE FTK UIN Ar-Raniry, 2021)
This research was conducted to identify the test of the water quality which good for consumption. It can be proved from temperature, turbidity level, and TDS (Total Dissolved Solids). By tempting the sensor, the turbidity and TDS meter controlled with the Arduino uno and the MCU node is forwarded to send data to the bylink application. The bylink application will help in monitoring water conditions by displaying the water condition which fit for consuming. The method used in this research was started with making a prototype then producing data to determine the feasibility of water through the TDS sensor, temperature sensor, and NTU (water clarity). This indicators were developed on an Android system whom the user could determine feasibility water easier.